Refleksi Siswa dalam Pembelajaran dengan Scaffolding dari Mahasiswa Calon Guru - Kurniawati, Yeva; Triyana, Illah Winiati (Universitas Muhammadiyah Gresik, 2023)
This research aims to find out how the students' reflections on learning with scaffolding done by student teachers. To achieve the purpose of this research, a research design is used with the approach of concurrent embedded strategy of mixed methods with the research subjects being students of eleventh grade SMA Assaadah. The instruments used to collect data in this research are questionnare sheet and interview guide which have been declared valid by two experts. The results of data analysis show that the level of satisfaction of each statement of the learning reflection questionnaire with scaffolding answered by students, there are 10 items of the statement answered with a very satisfied index and 7 items of the statement answered with a satisfied index. The average of the satisfaction index results from all the student questionnaire’s answers is 3.32 which is in the criteria of very satisfied with the learning with scaffolding index. Based on the interview results, it is also known that scaffolding helps them to build a better understanding of how the learning process takes place. They can recognise that learning is a journey that involves trials, failures, and learning from mistakes. Students who receive scaffolding are more likely to appreciate the support they receive from the teacher. They can understand the important role of that support in helping them achieve a better understanding.Keywords: Reflection, Scaffolding, Student’s Satisfaction, Instructional